The Influence of Problem-Based Learning Models on Student Learning Outcomes on Dynamic Fluid Material - Jeffrey Payung Langi (Jurnal Syntax Transformation, 2024)
Thus studying physics is very important as it relates to real life. However, based on the results of a survey that has been carried out in a high school, it is known that student learning outcomes are less / low, this is due to difficulties in understanding fundamental physics concepts, limitations in solving physics problems, and lack of connections between these concepts. Therefore, the purpose of this study is to analyze how the implementation of the application of the PBL model for the learning outcomes of dynamic fluid material students. The method applied in this study is quantitative Quasi Experiment using nonequivalent control group design. From the results of research that has been carried out, it can be concluded that the PBL learning model has the potential to improve physical learning outcomes, especially in the context of Dynamic Fluid material. The implications of this research can be used as a basis to recommend the application of the Problem Based Learning model in physics learning to improve the effectiveness and efficiency of the concept understanding process at the relevant educational level. Further research can be conducted to explore specific aspects of this learning model that exert the most significant impact on understanding physics concepts.